2021
DOI: 10.1590/1806-9304202100s100009
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with psychic symptomatology in diabetics during the COVID-19 pandemic

Abstract: Objectives: to determine the frequency and factors associated with severe / extreme signs and symptoms of stress, anxiety and depression in diabetic patients during the COVID-19 pandemic. Methods: cross-sectional study conducted in April /May 2020, which included 162 individuals with diabetes mellitus and over 18 years old. An online questionnaire was applied on social networks, composed of biological, sociodemographic, clinical characteristics and the Stress, Anxiety and Depression Scale (DASS-21). For sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 20 publications
1
4
1
5
Order By: Relevance
“…Moreover, our findings corroborate what was discovered during the COVID-19 pandemic among diabetic patients in Brazil [ 20 ]; 43.3% of participants had anxiety while 45.1% of participants had depression. Our study discovered that depression rates were likewise similar to those observed in Bangladeshi patients with chronic diseases [ 21 ]; 59% of participants had anxiety while 71.6% of participants had depression.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, our findings corroborate what was discovered during the COVID-19 pandemic among diabetic patients in Brazil [ 20 ]; 43.3% of participants had anxiety while 45.1% of participants had depression. Our study discovered that depression rates were likewise similar to those observed in Bangladeshi patients with chronic diseases [ 21 ]; 59% of participants had anxiety while 71.6% of participants had depression.…”
Section: Discussionsupporting
confidence: 89%
“…The sociodemographic and clinical characteristics of the participants in this study diverge from those found in other studies conducted with people living with DM during social distancing in the COVID-19 pandemic, in which there is predominance of users with undergraduate/graduate degrees, aged between 30 40 years old and self-declared white skin [10][11] .…”
Section: Discussioncontrasting
confidence: 91%
“…It is important to emphasize that, as a result of the pandemic, many people were affected by work-related modifications and by changes in the family income. This is proven in an research study whose data showed that 43.2% of the participants had their monthly family income reduced 11 . In addition to the elements herein presented, a research study that investigated mental health and work attitudes among people who returned to work during the COVID-19 pandemic pointed out that the main risk factor for mental health impairment was concern with unemployment, as being unemployed meant losing their source of income and not having financial security 30 .…”
Section: /14mentioning
confidence: 86%
“…Factors reported to be associated with the presence of depressive symptoms in diabetic patients during the COVID-19 pandemic included female gender [ 30 , 32 , 36 , 38 , 39 , 40 , 41 , 42 ], being single [ 38 , 41 ], the absence of religious faith [ 41 ], lower education level [ 38 ], smoking [ 40 ], a history of anxiety and/or depression [ 41 ], lower income [ 41 ] and part-time work or remote study [ 41 ]. In relation to age, some authors indicate that younger age is a predisposing factor [ 28 , 32 , 38 ] while others found no significant relationship [ 39 ] ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%